Az anyanyelv-elsajátítás és az idegennyelv-tanulás összefüggéseinek megközelítései: Egy közös értelmezési keret lehetősége - Sominé Hrebik, Olga (Magyar Pedagógia, 2011)
This paper provides a comprehensive overview of the various approaches to language learning from the perspectives of (1) better understanding the relationship between L1 and L2 acquisition and (2) exploring additional factors influencing language acquisition. After a brief summary of the classical theories of language acquisition, the characteristics of first language acquisition are described in detail. The second section discusses the links, similarities and differences between L1 and L2 acquisition. The third section of the paper describes the obstacles to acquiring a second language to native-like proficiency, while the fourth section reviews the effect of age on language learning. The fifth section summarizes attempts to construct a comprehensive model of foreign language learning. Finally, the sixth section introduces a synthesized model of the various approaches. The model is constructed to display the factors that impact L1 and L2 acquisition and the relationships between the informal acquisition of the mother tongue and the formal learning of foreign/second languages. This review of the major factors in language learning and exploration of their nature and functioning may contribute to the development of the practice of foreign/second language teaching.